Explaining European Union Citizens' Trust in the European Central Bank in Normal and Crisis Times1. (19th June 2013) - Ehrmann, Michael; Soudan, Michel; Stracca, Livio
Abstract We study the determinants of trust in the European Central Bank (ECB) as measured by the European Commission's Eurobarometer survey, in particular during the global financial crisis and the European sovereign debt crisis. We find that the fall in trust in the ECB in crisis times can be rather well explained based on the pre‐crisis determinants. We also show that the fall in trust reflected the macroeconomic deterioration, a more generalized fall in the trust in European institutions in the wake of the crisis, and the severity of the banking sector's problems, to which the ECB was associated in the public opinion.